Community and household shocks: Findings from the seventh round of the Myanmar Household Welfare Survey (January–June 2024) - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
The seventh round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between April and June 2024. It follows six rounds that were carried out since the beginning of December 2021. This report discusses the findings from the seventh round related to shocks including conflict, climatic, service sector, and economic. The security situation in Myanmar continued to worsen during the seventh-round recall period, which spanned from January to June 2024. Households felt insecure in their communities, as reported by 23 percent of households, and had low levels of trust in their communities, as reported also by 23 percent of households. This is because crime and violence remained high, affecting 16 and 9 percent of communities, respectively. Lawlessness continues to be a widespread issue in Myanmar. In January–June 2024, 18 percent of households reported a lot or some gambling in their community and 13 percent reported drug use. These issues were more prominent in urban areas, compared to rural areas. A new challenge is risk of conscription, reported by 39 percent of households. Another crucial challenge is that 13 percent of respondents felt that it was dangerous for them to move around and do everyday tasks. Finally, three percent of respondents revealed that there was a risk of kidnapping in their community.